-
If a = 2 + √3 , then the value of a6 + a4 + a2 + 1 is a3
-
- 45
- 65
- 42
- 56
- 45
Correct Option: D
a = 2 + √3
⇒ | = | ||
a | 2 + √3 |
⇒ | = | ||
a | ( 2 + √3 )( 2 - √3 ) |
⇒ | = | = 2 - √3 | ||
a | 4 - 3 |
∴ a + | = 2 + √3 + 2 - √3 = 4 | |
a |
∴ Expression = | ||
a3 |
Expression = a3 + a + | + | ||
a | a3 |
Expression = a3 + | + a + | ||
a3 | a |
Expression = | ![]() | a + | ![]() | 3 | - 3 | ![]() | a + | ![]() | + | ![]() | a + | ![]() | |||
a | a | a |
Expression = | ![]() | a + | ![]() | 3 | - 2 | ![]() | a + | ![]() | ||
a | a |
Expression = (4)3 – 2 × 4 = 64 – 8 = 56